Cost-effective asset management planning for the sustainable future of rural irrigation systems - Ika Kustiani (Curtin University, 2014)
Irrigation systems in developing countries often have low performance and poor sustainability. The asset management planning (AMP) model that has been developed in this project enables Water User Associations (WUAs) in rural Indonesia to manage the assets of a transferred irrigation system in an improved cost-effective way towards sustainability goals. The AMP was developed by building on existing processes and including elements of internationally developed assest management sytems and also with upgraded physical and management processes.